CARDIAC ARREST AND BASIC LIFE SUPPORT FOR THE GENERAL PUBLIC - Fithriany, Fithriany; Laila, Nurnarita; Kusuma, Nila; Fadlina, Amelia (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Cardiac arrest is a condition in which the heart stops pumping blood effectively, resulting in loss of consciousness and potentially causing death if not treated quickly and appropriately. Knowledge about cardiac arrest and proper first aid measures is very important for the general public, because this incident can happen anytime and anywhere. Cardiac arrest can be caused by coronary heart disease, arrhythmia, or other medical conditions. When cardiac arrest occurs, blood flow to the brain and other vital organs stops, requiring immediate treatment to provide a chance of survival. Basic Life Support (BLS) is a series of actions taken to maintain the function of vital organs of cardiac arrest victims until professional medical assistance arrives. BLS training is very important for the general public so that they can provide first aid in emergency situations. With the right knowledge of how to do BLS and recognize the signs of cardiac arrest, they can contribute to saving lives. Training methods include lectures, interactive discussions, and practicing BLS techniques correctly. The conclusion is that increasing awareness and knowledge about cardiac arrest and Basic Life Support among the general public is a crucial step in saving lives. With the right training, every individual has the potential to be an effective first responder in an emergency situation. Keywords: Cardiac arrest, BHD, lay public